2020
DOI: 10.1177/0194599820947001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Complications Occurrence Associated With Emergency Surgical Tracheotomy

Abstract: Objective In emergency airway management, the occurrence of surgical tracheotomy complications is increased and may be fatal for the patient. However, the factors that play a role in complication occurrence and lead to lethal outcome are not known. The objective of this study was to determine predictors associated with the occurrence of complications and mortality after emergency surgical tracheostomy. Study Design Retrospective study with a systematic review of the literature. Setting Tertiary medical academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
12
1
3
Order By: Relevance
“…There was a significantly important correlation of the presence of pathogenic microorganisms and tracheostoma infection (p=0.00) determined for the whole sample, and after a subsequent testing, it was determined that this correlation results from statistically significant correlation of the presence of pathogenic microorganisms and the infection of tracheostoma only in group A patients. The rate of individual complications in our study was between 3.9% to 25% which does not differ significantly from the published figures in the literature ranging from 5.6% to 27.2% (35)(36)(37)(38)(39)(40). The incidence of overall tracheotomy complications in COVID-19 patients is higher than in the general population.…”
Section: Discussioncontrasting
confidence: 53%
“…There was a significantly important correlation of the presence of pathogenic microorganisms and tracheostoma infection (p=0.00) determined for the whole sample, and after a subsequent testing, it was determined that this correlation results from statistically significant correlation of the presence of pathogenic microorganisms and the infection of tracheostoma only in group A patients. The rate of individual complications in our study was between 3.9% to 25% which does not differ significantly from the published figures in the literature ranging from 5.6% to 27.2% (35)(36)(37)(38)(39)(40). The incidence of overall tracheotomy complications in COVID-19 patients is higher than in the general population.…”
Section: Discussioncontrasting
confidence: 53%
“…For the two dying of MG crisis in the control group, there seemed no direct associations with medications regarding the normal therapies they received. Failure to quickly identify the impending respiratory paralysis and complex comorbid conditions could explain the death of an outbreak at home; the other patient died from tracheotomy-related death together with MG crisis, unresponsive wakefulness syndrome, and pneumonia, all being hazard factors for tracheotomy complications ( 38 ). We need to focus more on the prevention of myasthenia crisis, which is typically precipitated by poor control of generalized MG.…”
Section: Discussionmentioning
confidence: 99%
“…However, this should be balanced by the associated risks. Jotic et al identified several predictors of perioperative morbidity and mortality in patients undergoing emergency OST [42]. Attention must be paid in the case of patients that previously underwent tracheotomy or neck radiotherapy, or in those with pathologies of the neck.…”
Section: Esa: Should Emergency Tracheotomy Be Preferred Over Cricothymentioning
confidence: 99%
“…Despite the higher incidence of perioperative complications of OST procedure performed in non-operating theatre context [42], most authors recommend avoiding the transport of patients between different hospital services because of the high risk of viral contamination. In those cases in which the patient's transfer appears unavoidable, reserved routes should be used.…”
Section: Location and Personnel Involvedmentioning
confidence: 99%